2020
DOI: 10.5888/pcd17.200125
|View full text |Cite
|
Sign up to set email alerts
|

Health and Health Determinant Metrics for Cities: A Comparison of County and City-Level Data

Abstract: What is already known on this topic? Many local health departments develop city-level public health policies but lack city-level health data. This lack causes reliance on county-level data, which may misrepresent city populations. What is added by this report? We found substantial and highly variable city-county differences within and across 4 public health metrics, suggesting use of county-level data may mischaracterize health metrics in cities. What are the implications for public health practice? Use of cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 8 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…For example, cities like Santiago (Chile) and Chicago (US) have differences in life expectancy within their own neighbourhoods of 17.7 and 30 years, respectively. 42 , 43 Therefore, several cities have committed to minimizing health inequalities and ensuring that every citizen reaches their health potential, in part through the support of digital health.…”
Section: Which Steps Should Be Undertaken To Make Digital Health Acce...mentioning
confidence: 99%
“…For example, cities like Santiago (Chile) and Chicago (US) have differences in life expectancy within their own neighbourhoods of 17.7 and 30 years, respectively. 42 , 43 Therefore, several cities have committed to minimizing health inequalities and ensuring that every citizen reaches their health potential, in part through the support of digital health.…”
Section: Which Steps Should Be Undertaken To Make Digital Health Acce...mentioning
confidence: 99%
“…While county-level data are essential for public health surveillance and planning, city and sub-city data are vital to guide local pandemic response efforts, particularly because more than 80% of the U.S. population lives in urban areas ( U.S. Census Bureau, 2021 ). City populations often differ substantially from the populations of counties in which they are located, causing county-level metrics to be insufficient proxies for city-level measures ( Spoer et al, 2020 ). This is consistent with Tobler's first law of geography, which states “everything is related to everything else, but nearer things are more related than distant things”.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the use of more readily available county level data is not an appropriate proxy and that programs operating on the city level should be informed by city level data [13]. City-level surveillance systems are more effective at reporting timely influenza/pneumonia mortality data which can be used during outbreaks and provide practical applications for the development of public health measures [14].…”
Section: Introductionmentioning
confidence: 99%